Neuropsychological rehabilitation: a behavioral reading (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Neuropsychological rehabilitation is one component in treatment of clients with cerebral lesions and/or neurological and neuropsychiatric disturbances. Rehabilitation programs benefit from the application of behavioral procedures, primarily because the science of behavior analysis offers invaluable tools to the modification of behavior and learning processes. OBJECTIVES: The present paper aims to discuss the interaction between the fields of neuropsychological rehabilitation and behavior analysis. METHODS: The discussion is based on an overview of neuropsychological rehabilitation and on the clarification of behavioral procedures' use in both neuropsychological assessment and rehabilitation. RESULTS: Thus, the paper tries to clarify necessary precautions required in planning a treatment program. Interest about the development of further research in this field and about the pursuit of basic knowledge in behavior analysis is expected to take place. DISCUSSION: This result seems to reflect not the scarcity of studies about behavioral procedures application in neuropsychological rehabilitation programs. However, it may indicate that there is a lack of clarity by rehabilitation professionals that many procedures used in rehabilitation programs are behavioral procedures. Or it can also mean that behavioral neuropsychology is a rather unknown field, or yet, it might only reflect the prejudice that behavior analysis has been suffering along the years.